Pengaruh Geometri Jalan terhadap Konsumsi Bahan Bakar Alat Angkut pada Penambangan Batubara - Nabilla Amellia Putri; Iswandaru; Elfida Moralista (Jurnal Riset Teknik Pertambangan, 2025)
Abstract. PT Bara Selaras Resources is a coal mining company with an open-pit mining system and a production target of 250,000 tons/month. However, production in May and June 2024 only reached 178,236 tons and 177,498 tons. In addition, the fuel ratio exceeded the maximum limit of 0.22 liters/BCM, reaching 0.29 liters/BCM in May and 0.27 liters/BCM in June. This issue is suspected to be due to the road geometry not complying with the standards of the Minister of Energy and Mineral Resources Decree No. 1827K/30/MEM/2018 and the AASHTO standards.This study aims to analyze the influence of road geometry on fuel consumption and transport equipment productivity. The study was conducted on a 1.96 km coal transport road divided into 33 segments, with an evaluation of road width, grade, cross slope, and superelevation based on the standards of the Minister of Energy and Mineral Resources Decree No. 1827K/30/MEM/2018 and AASTHO.The research results show that after the repairs, the productivity of the transport equipment increased by 18.32% from 67.76 BCM/hour/unit to 82.96 BCM/hour/unit. The fuel ratio decreased by 43.75% from 0.23 liters/BCM to 0.16 liters/BCM. Production increased by 22.53% from 221,825.49 tons to 271,584.20 tons, thus achieving the production target. Abstrak. PT Bara Selaras Resources merupakan perusahaan tambang batubara dengan sistem tambang terbuka dan target produksi 250.000 ton/bulan. Namun, produksi pada Mei dan Juni 2024 hanya mencapai 178.236 ton dan 177.498 ton. Selain itu, fuel ratio melebihi batas maksimum 0,22 liter/BCM, yaitu 0,29 liter/BCM pada Mei dan 0,27 liter/BCM pada Juni. Masalah ini diduga akibat geometri jalan yang tidak sesuai dengan standar Keputusan Menteri ESDM No. 1827K/30/MEM/2018 tentang Pedoman Pelaksanaan Kaidah Teknik Pertambangan yang Baik dan standar American Association of State Highways and Transportation Officials (AASTHO). Penelitian ini bertujuan untuk menganalisis pengaruh geometri jalan terhadap konsumsi bahan bakar dan produktivitas alat angkut. Studi dilakukan pada jalan angkut batubara sepanjang 1,96 km yang terbagi dalam 33 segmen, dengan evaluasi terhadap lebar jalan, grade, cross slope, dan superelevasi berdasarkan standar Keputusan Menteri ESDM No. 1827K/30/MEM/2018 dan AASTHO. Hasil penelitian menunjukkan bahwa setelah perbaikan, produktivitas alat angkut meningkat 18,32% dari 67,76 BCM/jam/alat menjadi 82,96 BCM/jam/alat. Fuel ratio menurun 43,75% dari 0,23 liter/BCM menjadi 0,16 liter/BCM. Produksi meningkat 22,53% dari 221.825,49 ton menjadi 271.584,20 ton, sehingga target produksi tercapai.